Caracterização parcial e imobilização de fosfatase produzida por Pluralibacter gergoviae - Valencia Mejía, Erika (2015)
Phosphorus is a nutritional limiting factor for plant growth but over 80% of the phosphorus applied directly to the soil becomes unavailable due to adsorption, precipitation or assimilation to organic phosphorus. One plant’s strategy to obtain phosphate from soils is mediated by the action of phosphatase enzymes, which catalyze hydrolysis of phosphate esters producing soluble phosphorus. In this study, a phosphate-solubilizing microorganism from Cerrado soil was used as phosphatase producer. The produced phosphatase was partially characterized and immobilized in different soil fractions. The microorganism that showed the highest phosphatase activity was identified as Pluralibacter gergoviae with a specific activity of 27.43 U/mg. The optimal activity of phosphatase produced by P. gergoviae was found at pH 5.2 and a temperature of 55°C. The effect of common inhibitors show that calcium and magnesium did not interfere in the phosphatase activity, whereas inorganic phosphate, ammonium and potassium slightly inhibited the enzyme activity. The best results of immobilization were obtained in the tests with silica and the organic fraction, which presented 44% of immobilization yield. Therefore, the immobilization of acid phosphatase produced by P.gergoviae in soil fractions might be an promising alternative for increasing the inorganic phosphate content in soil, which might contributes to the enhancing the agricultural productivity.